Local biomass burning is a dominant cause of the observed precipitation reduction in southern Africa - Øivind Hodnebrog (Nature Portfolio, 2016)
Black carbon aerosols in the atmosphere absorb solar radiation and affect the hydrological cycle. Here, the authors show that local aerosol emissions from biomass burning activities are a main cause of observed decline in southern African dry season precipitation over the last century.